(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
Postmodernism cannot be fully understood without a solid understanding of modernism, particularly its development in literature. Modernism emerged in the early twentieth century and gained significant influence after the First World War, reflecting the rapid social, technological, and industrial changes of the time. Modernist writers grappled with a fragmented and unstable world in which traditional values and predictable structures had collapsed. As a result, modernist literary works often expressed feelings of alienation, despair, and absurdity, while simultaneously seeking to restore meaning to human existence. These works were frequently characterized by fragmented narratives, incoherent meanings, and a crisis of personal identity. An additional and significant aspect of modernism is its ambiguous relationship with colonialism.